(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2014)
Metformin HCl microspheres were prepared with the aim of increasing its bioavailability and decreasing gastrointestinal side effects by means of sustained action. Eudragit RSPO and Eudragit RLPO, polymers of different permeability characteristics were used to prepare different microspheres. Emulsification solvent evaporation technique using acetone as the internal phase and liquid paraffin as the external phase was the method of choice. Six formulations were prepared using two polymers. The effect of drug loading and polymeric property on the surface morphology, entrapment efficiency, particle size and release characteristics of the microspheres were examined. FTIR and DSC studies established compatibility of the drug with the polymers. SEM studies clearly revealed the effect of drug loading and polymeric nature on the surface morphology of the microspheres. Entrapment efficiencies were within 77.09-97.11% and particle size of all the batches were in the acceptable range. Release data were treated with different mathematical kinetic models. The drug release profile showed that Eudragit RSPO and Eudragit RLPO have opposite effect on drug release. On the other hand, increase in drug loading results in increased drug release. Kinetic modeling of in vitro dissolution profiles revealed that the drug release mechanism varies from diffusion controlled to anomalous type. Dhaka Univ. J. Pharm. Sci. 12(2): 131-141, 2013 (December) DOI: http://dx.doi.org/10.3329/dujps.v12i2.17611